Oxidized hyaluronic acid cross-linked collagen hydrogel as well as preparation method and application thereof
By cross-linking and composite encapsulation with oxidized hyaluronic acid, a stable collagen hydrogel was prepared, which solved the problems of short-term decline in the filling effect and safety of collagen implants, and achieved long-lasting maintenance and safe cosmetic application.
Patent Information
- Application Number
- CN202511378458.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-25
- Publication Date
- 2025-10-28
- Estimated Expiration
- 2045-09-25
AI Technical Summary
Existing collagen implants have a problem where the filling effect is good but the implant falls back after 1-2 weeks. This is mainly due to collagenase decomposition and metabolism and dehydration and coagulation. In addition, the residue of cross-linking agents may cause cytotoxicity or immune response.
The preparation method of collagen hydrogel crosslinked with oxidized hyaluronic acid includes pretreatment, high-pressure homogenization, crosslinking with oxidized hyaluronic acid, compounding with sulfonated chitosan and coating with trehalose, forming a stable triple hydration network structure, which enhances the collagen's resistance to enzymatic hydrolysis and hydration.
It achieves long-lasting maintenance of collagen hydrogel, avoids dehydration and sagging, reduces the safety risks of cross-linking agents, improves mechanical strength and thermal stability, and reduces water migration.
Smart Images

Figure SMS_3 
Figure SMS_4 
Figure SMS_5
Abstract
Description
Technical Field
[0001] This invention relates to the field of biomaterials technology, specifically to a collagen hydrogel crosslinked with oxidized hyaluronic acid, its preparation method, and its application. Background Technology
[0002] Collagen is a naturally occurring protein in the human body, possessing a triple helix structure with a repeating amino acid sequence (Gly-XY), low immunogenicity, complete biodegradability, and the ability to promote cell proliferation, adhesion, and differentiation as a cell scaffold, making it an ideal soft tissue filler. Currently, several collagen implants are available on the market both domestically and internationally, mainly of two types: non-crosslinked and crosslinked. Non-crosslinked collagen implants, such as those with Chinese patents CN115572328A and CN116103776A, have short-lasting effects. This is generally considered to be mainly due to the decomposition and metabolism of collagenases in the human body. Therefore, researchers have improved collagen's resistance to enzymatic degradation through various crosslinking methods. For example, glutaraldehyde, a commonly used chemical crosslinking agent in commercially available products, has a glutaraldehyde aldehyde group (-CHO) that can bind to the free amino groups (-NH2) on the peptide chains of collagen to form intramolecular or intermolecular Schiff base covalent crosslinks. This crosslinking significantly enhances collagen's resistance to enzymatic degradation, thermal stability, and mechanical strength. For example, Chinese patent CN115747993A discloses a collagen fiber with high biocompatibility and high stability, its preparation method and application. It uses the chemical reagent NHS-SA to crosslink with collagen, but its anti-enzymatic effect is not good and its improvement on filling and maintenance effect is limited.
[0003] While some progress has been made in the basic research on sodium oxidized hyaluronic acid as a crosslinking agent in existing technologies, such as the self-crosslinking hydrogel of chitosan polypeptide derivatives using sodium oxidized hyaluronic acid as a crosslinking agent disclosed in Chinese patent application CN111019162A, and the hydrogel formed by crosslinking collagen and sodium oxidized hyaluronic acid in Chinese patent application CN120305450A, this hydrogel can only be used externally for wound repair and cannot be used as an implant. Existing crosslinked collagen still faces technological gaps in terms of safety and precise control of residue levels. Residual free aldehyde groups may trigger cytotoxicity or immune responses, and may even non-specifically bind to other biomolecules in the body, leading to local tissue inflammation or decreased material stability.
[0004] Currently, both non-crosslinked and crosslinked collagen implants have good immediate filling effects, but the filling effect tends to decline after 1-2 weeks. The main reason for this is not only that the collagen is broken down and absorbed by collagenase, but also that dehydration and aggregation occur after implantation. The saline solution in the implant is also rapidly absorbed by the body, resulting in a reduction in the filling volume of the implant. Often, it is necessary to inject again to achieve the desired effect for the patient. Summary of the Invention
[0005] Therefore, the present invention provides a collagen hydrogel crosslinked with oxidized hyaluronic acid, its preparation method and application, to solve the problems in the prior art.
[0006] To achieve the above objectives, the present invention provides the following technical solution: According to one aspect of the present invention, a method for preparing a collagen hydrogel crosslinked with oxidized hyaluronic acid includes the following steps: Step 1, Collagen Pretreatment The collagen solution was adjusted to its isoelectric point, stirred to precipitate, and centrifuged to obtain the precipitate. The precipitate was then washed by repeated centrifugation with buffer solution to obtain crude collagen fiber precipitate. The crude collagen fiber precipitate was reconstituted with acetic acid solution, and pepsin solution was added to react. After the reaction was completed, the precipitate was purified to obtain pretreated collagen. Step 2, Preparation of collagen homogenate The pretreated collagen was dissolved in buffer solution and then homogenized under high pressure using a high-pressure homogenizer to obtain a collagen homogenate. Step 3, Preparation of oxidized sodium hyaluronate Sodium hyaluronate solution was subjected to aldehyde reaction with sodium periodate, the reaction was terminated by adding ethylene glycol, and then concentrated by ultrafiltration and lyophilized to obtain oxidized hyaluronic acid. Step 4, Preparation of hydrogel Oxidized hyaluronic acid was dissolved in a buffer solution to obtain an oxidized hyaluronic acid solution. Collagen homogenate was added to the solution to carry out a cross-linking reaction to form a solidified hydrogel. After washing to remove residual unreacted oxidized hyaluronic acid, the initial hydrogel was obtained. The initial hydrogel was then coated with sulfonated chitosan and trehalose to obtain a hydrogel block, which is the collagen hydrogel.
[0007] Furthermore, the collagen used in this invention is derived from animals. In step one, the collagen is collagen extracted from animal Achilles tendons or animal skin. The collagen includes, but is not limited to, collagen extracted from pig Achilles tendons, pig skin, cow Achilles tendons, or cow skin. The collagen of this invention can be obtained commercially or prepared in-house.
[0008] Furthermore, in step one, the concentration of the collagen solution is 1-6 mg / mL.
[0009] The pH adjustment to the isoelectric point refers to adjusting the pH to 4.5-6.0. The pretreatment method of this invention utilizes collagen isoelectric point precipitation to remove acid-soluble impurities (albumin, glycoproteins, etc.) and concentrate collagen. At the collagen isoelectric point (pI≈4.5-6.0), the net surface charge of collagen molecules is zero, resulting in the lowest solubility and precipitation, while the impurities remain dissolved in the liquid phase. Preferably, the precipitation method involves stirring for 4-6 hours and then allowing it to stand at 4°C for 1.5-2.5 hours.
[0010] The pH adjuster of the present invention is one or more of sodium hydroxide, disodium hydrogen phosphate, sodium citrate, and citric acid.
[0011] Further, the collagen pretreatment step includes: adjusting the pH of the collagen solution to 4.5-6.0, stirring to precipitate, centrifuging to obtain the precipitate, and repeatedly centrifuging and washing with buffer solution to obtain crude collagen fiber precipitate; resolving the crude collagen fiber precipitate with acetic acid solution, stirring at 3-5℃, then adjusting the pH to 2-3, adding pepsin solution, and carrying out a constant temperature reaction; after the reaction is completed, terminating the reaction by adjusting the pH to inactivate pepsin, and purifying by tangential flow ultrafiltration to obtain pretreated collagen; wherein the centrifugation speed is 6000-10000 rpm and the centrifugation time is 15-20 min.
[0012] The collagen of the present invention is pretreated with pepsin, which selectively cleaves the terminal peptides of crude collagen fibers (pepsin specifically hydrolyzes the carboxyl-terminal peptide bonds of aromatic amino acids (Phe / Tyr) at pH 2-3), exposing the active sites of collagen.
[0013] As an example, the pepsin pretreatment method is as follows: Collagen crude fiber precipitate is reconstituted with 0.3M acetic acid, stirred at 4℃ for 12h, 2M HCl is added dropwise, and the pH is adjusted to 2.5±0.1 with magnetic stirring. Pepsin solution (pre-cooled 0.1M HCl) is added to a final concentration of 0.8% (w / w, enzyme / collagen), and the reaction is carried out at 4℃ with shaking at 50 rpm for 24h. After the reaction is completed, 1M sodium hydroxide solution is added to adjust the pH to 7 (to inactivate pepsin) to terminate the reaction. The collagen pretreated with pepsin is obtained by tangential flow ultrafiltration purification.
[0014] Furthermore, the tangential flow ultrafiltration purification step includes: centrifuging the reaction solution to obtain a precipitate, redissolving it with 0.05M HCl solution, and repeating the liquid exchange with 0.05M HCl solution 5-6 times under the conditions of 100 kDa MWCO, 4℃, transmembrane pressure 0.8 bar, and flow rate 5 L / min. Finally, adjusting the pH to 7 with 1M sodium hydroxide solution, centrifuging after collagen precipitation, and obtaining collagen pretreated with pepsin.
[0015] Furthermore, in step two, the high-pressure homogenization is carried out in three stages: the first stage pressure is 4000±100psi to break up large aggregates; the second stage pressure is 8000±100psi to dissociate fiber bundles; and the third stage pressure is 12000±100psi to obtain uniform nanofibers.
[0016] Furthermore, in step two, the high-pressure homogenization control temperature is 2-8℃, preferably 4℃.
[0017] Furthermore, in step two, the concentration of the collagen homogenate is 50-70 mg / mL.
[0018] Further, in step three, the mass concentration of the sodium hyaluronate solution is 0.5-5%, for example, it can be 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or any of the above values; preferably, the mass concentration of the sodium hyaluronate solution is 1%-4%.
[0019] Furthermore, the mass ratio of sodium hyaluronate to sodium periodate is 1:0.5-1:2.
[0020] Furthermore, in step two, the molecular weight of the sodium hyaluronate ranges from 400,000 to 2,600,000 Da, preferably sodium hyaluronate with a molecular weight greater than 1,200,000 Da.
[0021] Further, in step three, the mass concentration of the oxidized hyaluronic acid solution is 3%; the mass ratio of the collagen homogenate to the oxidized hyaluronic acid solution is 1:1-5:1, preferably 3:1. The cross-linking reaction temperature is 37℃, and the cross-linking reaction time is 1-3 hours.
[0022] Furthermore, in step three, the cleaning step includes: dividing the solidified hydrogel into portions with a volume of 0.1-1 cm³. 3 The small pieces of gel were soaked in PBS solution and stirred for 2-4 hours. The supernatant was removed by centrifugation, and the washing operation was repeated 3-5 times to obtain the initial hydrogel.
[0023] Furthermore, in step three, the step of sulfonated chitosan composite includes immersing the initial hydrogel in a sulfonated chitosan solution and obtaining a sulfonated chitosan composite hydrogel through vacuum negative pressure permeation; the step of trehalose coating includes placing the sulfonated chitosan composite hydrogel in a trehalose solution and treating it under vacuum negative pressure to obtain a hydrogel block.
[0024] Further, the steps of sulfonated chitosan composite include: soaking the initial hydrogel block in PBS buffer at 3-5℃, treating it with 0.1% EDTA solution, then adding it to a 30-50 g / L sulfonated chitosan solution, soaking it for 1-3 hours under vacuum of -0.08±0.01 MPa and temperature of 3-5℃, then raising the temperature to 25-27℃ and controlling the pH at 6.0±0.1, and reacting at a constant temperature. After the reaction is completed, rinsing with PBS buffer to remove unbound sulfonated chitosan, thereby obtaining sulfonated chitosan composite hydrogel.
[0025] As an example, the steps of the sulfonated chitosan composite include: soaking the initial hydrogel block in PBS buffer at 4°C for 30 min, treating it with 0.1% EDTA solution for 5 min, then adding it to a 40 g / L sulfonated chitosan solution, soaking it in a vacuum of -0.08 ± 0.01 MPa and a temperature of 4°C for 2 h, then raising the temperature to 26°C and controlling the pH at 6.0 ± 0.1, and reacting at a constant temperature for 12 h. After the reaction is completed, rinsing with PBS buffer to remove unbound sulfonated chitosan, and obtaining the sulfonated chitosan composite hydrogel.
[0026] Further, the trehalose coating step includes: placing the sulfonated chitosan composite hydrogel in a mixed solution containing 25-35 g / L trehalose, 0.1% hydroxypropyl methylcellulose, and 0.1 M PBS, controlling the temperature at 3-5°C, treating under negative pressure for 2-4 hours, and then allowing it to stand at normal pressure for 1-3 hours to obtain a hydrogel block.
[0027] As an example, the trehalose coating step includes: placing the sulfonated chitosan composite hydrogel in a mixed solution containing 30 g / L trehalose, 0.1% hydroxypropyl methylcellulose, and 0.1 M PBS, controlling the temperature at 4°C, treating it under a negative pressure of -0.1 MPa for 3 h, and then letting it stand at normal pressure (4°C) for 2 h to obtain a hydrogel block.
[0028] Furthermore, the buffer solution described in this invention is 0.9% sodium chloride or PBS buffer.
[0029] As an example, the hydrogel blocks obtained by the preparation method of the present invention can be freeze-dried or granulated by microporous extrusion to obtain gel microparticles with uniform particle size for use in different products.
[0030] According to another aspect of the present invention, a hydrogel prepared by the above-described method for preparing a collagen hydrogel crosslinked with oxidized hyaluronic acid is used in the preparation of a long-acting implant formulation.
[0031] The hydrogel obtained by this invention is mainly used in cosmetic products, including but not limited to long-acting implantable formulations for long-term volume enhancement and filling of facial tissues such as the forehead, tear troughs, cheekbones, nasolabial folds, and jaw.
[0032] The present invention has the following advantages: This invention, through pretreatment and high-pressure homogenization of collagen, can reduce the particle size of collagen fibers and decrease the steric hindrance of cross-linking reactions while maintaining the triple helix structure of collagen, making the cross-linking reaction more efficient, controllable, and uniform.
[0033] This invention utilizes a triple hydration network design, introducing hydrophilic HA groups through aldehyde-amino crosslinking, and anchoring water molecules through sulfonic acid groups via ionic bonds to increase the proportion of bound water. After trehalose coating, a glassy hydration layer is formed, reducing the migration rate of water molecules and solving the problem of dehydration and fallback of traditional collagen implants within 1-2 weeks.
[0034] This invention increases the cleaning area by segmenting the cross-linked hydrogel, and then washes it away by dynamic soaking in buffer solution followed by centrifugation. This removes free oxidized hyaluronic acid that did not participate in the cross-linking reaction, thus avoiding the unexpected safety risks of generating free aldehyde groups.
[0035] The oxidized hyaluronic acid crosslinked collagen hydrogel prepared by this invention has the advantages of high support, resistance to collagenase degradation and high hydration. It avoids rapid dehydration and coagulation of collagen suspension, maintains good immediate filling effect and also has long-term maintenance function. Detailed Implementation
[0036] The following specific embodiments illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0037] Collagen solution: Zhejiang Chongshan Biological Products Co., Ltd., 3mg / mL, containing telopeptide collagen solution (type I collagen). Pepsin: Sigma-Aldrich, enzyme activity titer ≥500U / mg; Sodium hyaluronate: Shandong Liyang Bioproducts Technology Co., Ltd., molecular weight 1.2 million Da; Sulfonated chitosan (SCS) solution: Sulfonated chitosan (Jiangzhou Biotechnology Co., Ltd., Taian City, JZ-20250402) was added to PBS and magnetically stirred for 2 hours until transparent to obtain a 40 g / L sulfonated chitosan solution; Carboxymethyl chitosan solution: Carboxymethyl chitosan (Shanghai Yuanye Biotechnology Co., Ltd., catalog number S30948) was added to PBS and magnetically stirred for 2 hours until transparent to obtain 40 g / L carboxymethyl chitosan; Trehalose: CAS 99-20-7; All other reagents are commercially available.
[0038] Example 1 This embodiment provides a method for preparing collagen hydrogel crosslinked with oxidized hyaluronic acid: (1) Collagen pretreatment A 3 mg / ml collagen solution was added to 0.5 M Na₂HPO₄ solution to adjust the pH to 4.5-6.0, stirred for 6 h to precipitate, allowed to stand at 4℃ for 1.5 h, centrifuged at 8000 rpm for 15 min, and washed three times with PBS solution to obtain crude collagen fiber precipitate. The crude collagen fiber precipitate was reconstituted with 0.3 M acetic acid, stirred at 4℃ for 12 h, and 2 M HCl was added dropwise. The pH was adjusted to 2.5±0.1 with magnetic stirring. Pepsin solution (pre-cooled 0.1 M HCl) was added to a final concentration of 0.8% (w / w, enzyme / collagen), and the reaction was carried out at 4℃ with shaking at 50 rpm for 24 h. After the reaction was completed, 1 M sodium hydroxide solution was added to adjust the pH to 7 (to inactivate pepsin) to terminate the reaction. The reaction solution was centrifuged to obtain the precipitate, which was then reconstituted with 0.05 M HCl solution and subjected to tangential flow ultrafiltration at 100 kDa MWCO, 4℃, transmembrane pressure 0.8 bar, and flow rate 5. Under the condition of L / min, the solution was changed 5-6 times with 0.05M HCl solution, and finally the pH was adjusted to 7 with 1M sodium hydroxide solution. After the collagen was precipitated, it was centrifuged to obtain collagen pretreated with pepsin.
[0039] (2) Preparation of collagen homogenate The pretreated collagen was diluted with PBS to a collagen solution of 60 mg / ml, stirred and mixed, and then homogenized using a high-pressure homogenizer. The high-pressure homogenization was carried out in three stages: the first stage pressure was 4000±100 psi; the second stage pressure was 8000±100 psi; and the third stage pressure was 12000±100 psi. The temperature was controlled at 4℃ to obtain a collagen homogenate.
[0040] (3) Preparation of oxidized hyaluronic acid 1.2 million Da sodium hyaluronate was dissolved in purified water to prepare a 1.5% sodium hyaluronate solution. Sodium periodate was added at a mass ratio of 1:1.5 and reacted at room temperature in the dark for 4 hours. Then, an equal volume of ethylene glycol was added to quench the reaction, and the mixture was stirred at room temperature for 1 hour. The solution after the reaction was concentrated by ultrafiltration to remove residual small molecule impurities. The concentrated oxidized hyaluronic acid solution after ultrafiltration was frozen at -20°C for 4 hours, vacuum freeze-dried, and then stored in a sealed container at -20°C.
[0041] (4) Oxidized hyaluronic acid cross-linking gelation The lyophilized oxidized hyaluronic acid was dissolved in PBS solution to prepare a 3% oxidized hyaluronic acid solution. The collagen homogenate was added to the oxidized hyaluronic acid solution at a mass ratio of 3:1. After stirring evenly, the solution was incubated at 37°C for 2 hours to form a solidified hydrogel. The cured hydrogel was divided into sections with a volume of 0.5 cm³. 3 The gel pieces were soaked in PBS solution and stirred slowly for 2 hours. The supernatant was discarded by centrifugation using a high-speed centrifuge. The washing operation was repeated 3 times to obtain the initial hydrogel pieces. The initial hydrogel block was soaked in PBS buffer at 4℃ for 30 min, then treated with 0.1% EDTA solution for 5 min, and then added to 40 g / L sulfonated chitosan solution. It was soaked for 2 h under vacuum of -0.08±0.01 MPa and temperature of 4℃. Then the temperature was increased to 26℃ and the pH was controlled at 6.0±0.1. The reaction was carried out at a constant temperature for 12 h with shaking (50 rpm). After the reaction was completed, it was washed 3 times with PBS buffer to remove unbound sulfonated chitosan and obtain sulfonated chitosan composite hydrogel. The sulfonated chitosan composite hydrogel was placed in a mixed solution containing 30 g / L trehalose, 0.1% hydroxypropyl methylcellulose, and 0.1 M PBS. The temperature was controlled at 4°C, and the hydrogel was treated under a negative pressure of -0.1 MPa for 3 hours. Then, it was allowed to stand at normal pressure for 2 hours to obtain the hydrogel block, which is the collagen hydrogel. (5) Preparation of implantable formulation products The hydrogel block was extruded and granulated using a microparticle granulator, with a micropore diameter of 200µm. It was then filled into pre-filled syringes at a rate of 1g / vial, and sealed with a rubber piston after filling to obtain the finished implantable formulation.
[0042] Example 2 This embodiment provides a method for preparing collagen hydrogel crosslinked with oxidized hyaluronic acid: The concentration of sodium oxidized hyaluronic acid solution in step (4) was adjusted: the lyophilized oxidized hyaluronic acid was dissolved in PBS solution to prepare a 1% oxidized hyaluronic acid solution. Collagen homogenate was added to the collagen homogenate solution at a mass ratio of 3:1. After stirring evenly, the solution was incubated at 37°C for 2 hours to form a solidified hydrogel.
[0043] The remaining steps are the same as in Example 1.
[0044] Example 3 This embodiment provides a method for preparing collagen hydrogel crosslinked with oxidized hyaluronic acid: The concentration of sodium oxidized hyaluronic acid solution in step (4) was adjusted: the lyophilized oxidized hyaluronic acid was dissolved in PBS solution to prepare a 5% oxidized hyaluronic acid solution. Collagen homogenate was added to the collagen homogenate solution at a mass ratio of 3:1. After stirring evenly, the solution was incubated at 37°C for 2 hours to form a solidified hydrogel.
[0045] The remaining steps are the same as in Example 1.
[0046] Example 4 This embodiment provides a method for preparing collagen hydrogel crosslinked with oxidized hyaluronic acid: The preparation method of the implanted formulation in step (5) is adjusted as follows: After extrusion granulation, instead of pre-filling and sealing the syringes, conventional freeze-drying is used (trehalose is used as a freeze-drying protectant, freezing conditions: rapid freezing at -80℃, -40℃ / 0.1mbar) to obtain freeze-dried hydrogel with the following pore size distribution: 70% of the pores are 10-50μm micropores and 30% are >100μm macropores. It can be reconstituted before use.
[0047] The remaining steps are the same as in Example 1.
[0048] Comparative Example 1 This comparative example provides a method for preparing collagen hydrogel crosslinked with oxidized hyaluronic acid: Step (1) does not involve pepsin pretreatment; the remaining steps are the same as in Example 1.
[0049] Comparative Example 2 This comparative example provides a method for preparing collagen hydrogel crosslinked with oxidized hyaluronic acid: Step (2) does not involve high-pressure homogenization; otherwise, it is completely consistent with Example 1.
[0050] Comparative Example 3 This comparative example provides a method for preparing collagen hydrogel crosslinked with oxidized hyaluronic acid: Step (3) Sodium hyaluronate is not oxidized, but otherwise it is completely consistent with Example 1.
[0051] Comparative Example 4 This comparative example provides a method for preparing collagen hydrogel crosslinked with oxidized hyaluronic acid: Step (4) does not involve sulfonated chitosan composite treatment; otherwise, it is completely consistent with Example 1.
[0052] Comparative Example 5 This comparative example provides a method for preparing collagen hydrogel crosslinked with oxidized hyaluronic acid: Step (4) does not involve trehalose coating, but is otherwise completely consistent with Example 1.
[0053] Comparative Example 6 This comparative example provides a method for preparing collagen hydrogel crosslinked with oxidized hyaluronic acid: Step (4) involves carboxymethyl chitosan composite treatment, and the rest is completely consistent with Example 1.
[0054] Experimental Example 1 The relevant parameters of the embodiments and comparative examples were tested: 1. Collagen Content: The collagen content was determined using the biuret method. 1.0 g of hydrogel was accurately weighed and dissolved in 0.5 M acetic acid solution, then diluted to 10 ml. After centrifugation, the supernatant was used as the test solution. Bovine serum albumin was used as the control group. 10 mg was accurately weighed and dissolved in water to prepare a standard reference solution. 0.0 ml, 0.2 ml, 0.4 ml, 0.6 ml, 0.8 ml, and 1.0 ml of the standard reference solution were accurately measured and placed in stoppered test tubes. Water was added to each tube to a final volume of 1.0 ml, followed by 4.0 ml of biuret solution. The mixture was immediately mixed and allowed to stand at room temperature for 30 minutes. The absorbance was measured at 540 nm using a UV spectrophotometer. 1.0 ml of the test solution was also accurately measured and processed using the same method. The protein concentration in the test solution was calculated from the linear regression equation and multiplied by the dilution factor.
[0055] 2. Degree of crosslinking: The degree of crosslinking was tested using the trinitrobenzenesulfonic acid method. 0.25 g of crosslinked collagen hydrogel was weighed and brought to a final volume of 0.5 g with purified water. The mixture was dissolved in a solution containing 1 mL of 4% Na₂CO₃ and 1 mL of 0.5% 2,4,6-trinitrobenzenesulfonic acid (TNBS). The mixture was stirred at 220 r / min for 4 h at 40 °C. The same procedure was performed with 0.5 g of purified water and 0.25 g of uncrosslinked collagen hydrogel, serving as the blank control and the uncrosslinked control, respectively. 3 mL of 6 mol / L hydrochloric acid solution was added and the mixture was placed in an autoclave and heated at 120 °C for 1 h. The resulting solution was diluted with 5 mL of water and extracted three times with 20 mL of ether each time, discarding the ether layer. 5 mL of the aqueous phase was heated in a water bath for 15 min, cooled to room temperature, diluted with 15 mL of water, and the absorbance was measured at 346 nm.
[0056] ; In the formula, W0 is the absorbance of the blank control group; W1 is the absorbance of the uncrosslinked collagen hydrogel; and W2 is the absorbance of the crosslinked collagen hydrogel.
[0057] 3. Detection of residual sodium hyaluronate oxide: The carbazole colorimetric reaction method was used. 0.1 g of hydrogel was added to 9 g of PBS solution and extracted at 37°C for 24 hours. After centrifugation, 1 mL of the supernatant was used as the test solution. 10 mg of glucuronic acid was dissolved in water and diluted to 100 mL to prepare the standard solution. Accurately measure 0.0 mL, 0.2 mL, 0.4 mL, 0.6 mL, 0.8 mL, and 1.0 mL of the standard solution into stoppered test tubes, and add water to each to 1.0 mL. Place all standard solution tubes and sample tubes in an ice-water bath. Using an acid burette, slowly add 5 mL of 0.025 mol / L sodium tetraborate-sulfuric acid solution to each tube. After mixing, place in a boiling water bath for 20 min, then remove and cool to room temperature. Add 0.2 mL of carbazole ethanol solution to each tube, shake well, and place at room temperature for 2 h. Measure the absorbance of each standard tube and sample tube at 550 nm using a UV spectrophotometer. The glucuronic acid content in the test sample was calculated using a linear regression equation.
[0058] ; ρ—glucuronic acid content in the sample tube, in micrograms per milliliter (µg / ml); m2—Total mass of collagen hydrogel and PBS solution, in milligrams (mg). m1 — Mass of collagen hydrogel, in micrograms (µg).
[0059] 4. Thermal denaturation temperature Tm: After freeze-drying the collagen hydrogel, accurately weigh 5.0 mg and place it in a test aluminum pan. Under a nitrogen atmosphere, heat at a rate of 2℃ / min, and within the temperature range of 25-100℃, heat at a rate of 5℃ / min. Record the temperature value corresponding to the absorption peak of the sample.
[0060] 5. Rheological properties: Dynamic rheological measurements were performed using a rheometer in strain amplitude scanning mode at a fixed frequency of 10 rad / s, with a strain range of 0.1-1000%. The hydrogel was subjected to measurements within the linear viscoelastic region, with a frequency range of 1-100 rad / s, a constant strain of 1%, and a temperature of 25℃. The storage modulus (G') and loss modulus (G'') were recorded.
[0061] 6. Hydrogel volume loss rate experiment: After measuring the volume of collagen hydrogel, it was placed in PBS phosphate buffer at 37℃ for 7 days, and the hydrogel volume shrinkage rate was calculated.
[0062] 7. Cytotoxicity assay: Collagen hydrogel was extracted with 0.9% physiological saline as the test solution using the extraction method, and the effect of the extract on cell proliferation rate was determined by the CCK-8 assay.
[0063] 8. In vitro degradation experiment: The results were detected by using collagenase as the degradation enzyme in the in vitro degradation experiment, referring to the methods of YY / T0473 and GB / T16886.13.
[0064] The specific results are shown in Tables 1 and 2.
[0065] Table 1
[0066] Analysis of experimental results: The degree of cross-linking of collagen hydrogels is positively correlated with the concentration of sodium oxyhyaluronate. Increased cross-linking helps collagen fibers cross-link to form a more stable network structure, improving the collagen's resistance to enzymatic hydrolysis and thus enhancing the maintenance effect of soft tissue filling. However, with further increases in the concentration of sodium oxyhyaluronate solution, sodium oxyhyaluronate residues appear in the collagen hydrogel, causing difficulties in removal during actual production processes and the risk of residual free aldehyde groups. Therefore, a sodium oxyhyaluronate solution concentration of 1%-4% is preferred. High-pressure homogenized collagen slurry, due to its small particle size and low steric hindrance, facilitates cross-linking reactions. Sulfonated chitosan and trehalose coating enhance the thermal stability of the hydrogel through ionic and hydrated hydrogen bonds.
[0067] Table 2
[0068] Analysis of experimental results: The mechanical strength (storage modulus G' and loss modulus G''), thermal stability, and resistance to enzymatic hydrolysis of collagen hydrogels crosslinked with oxidized sodium hyaluronate are significantly improved compared to uncrosslinked collagen hydrogels. Comparative analysis of Example 1 with Comparative Examples 4 and 5 shows that hydrogels further solidified with sulfonated chitosan and trehalose enhance intermolecular forces, improve hydration capacity, and help reduce water absorption and loss under physiological conditions after implantation. Comparative analysis of Example 1 with Comparative Example 6 shows that sulfonated chitosan has a stronger ionic bonding ability than carboxymethyl chitosan, more effectively anchoring water molecules through ionic bonds, increasing the proportion of bound water, and forming a denser network structure, thus providing better mechanical support and resistance to dehydration, further reducing water absorption and loss under physiological conditions after implantation.
[0069] Experiment Example 2 In vivo injection experiment in rats: After one week of normal feeding, SD rats were used for an in vivo injection experiment. Rats were anesthetized with chloral hydrate, their backs were shaved and disinfected with 75% alcohol, and four injection points were symmetrically selected along the middle of the back, injecting 1 mL of collagen hydrogel at each point. After injection, the rats were fed normally, and the degree of back swelling was observed. Dissection observations were conducted at 1 week, 1 month, 3 months, and 6 months after implantation. Rats were euthanized by cervical dislocation and dissected, and the average residual volume of collagen hydrogel was recorded. The results are shown in Table 3.
[0070] Table 3
[0071] Analysis of experimental results: According to the degradation results in rats, the collagen hydrogel cross-linked with oxidized sodium hyaluronate of this invention can significantly improve the phenomenon of dehydration and coagulation of collagen hydrogel one week after implantation. Furthermore, the cross-linked collagen hydrogel maintains its performance for a longer time in rats, consistent with the trend of improved resistance to enzymatic degradation after cross-linking. In addition, comparative analysis shows that the particle size of the collagen hydrogel is also an important factor affecting its mechanical strength and maintenance time; larger particle sizes provide better support and maintenance. In Example 3, rats experienced slight skin redness in the early implantation stage. Based on the results in Table 2, it can be seen that the presence of residual free aldehyde groups in Example 3 caused cytotoxicity and some skin irritation. In Comparative Example 1, rats also experienced slight skin redness in the early implantation stage. The collagen hydrogel in Comparative Example 1 was not treated with pepsin, and its terminal peptides at both ends of the collagen peptide chain possess certain immunogenicity. Since the skin is a sensitive area, allergic reactions may occur. Therefore, collagen hydrogels treated with pepsin to remove terminal peptides are more preferred.
[0072] Although the present invention has been described in detail above with general descriptions and specific embodiments, modifications or improvements can be made to it, which will be obvious to those skilled in the art. Therefore, all such modifications or improvements made without departing from the spirit of the present invention fall within the scope of protection claimed by the present invention.
Claims
1. A method for preparing a collagen hydrogel crosslinked with oxidized hyaluronic acid, characterized in that, Includes the following steps: Step 1, Collagen Pretreatment The collagen solution was adjusted to its isoelectric point, stirred to precipitate, and centrifuged to obtain the precipitate. The precipitate was then repeatedly centrifuged and washed with buffer solution to obtain crude collagen fiber precipitate. The crude collagen fiber precipitate was redissolved in acetic acid solution, and then pepsin solution was added to react. After the reaction was completed, the collagen was purified to obtain pretreated collagen. Step 2, Preparation of collagen homogenate The pretreated collagen was dissolved in buffer solution and then homogenized under high pressure using a high-pressure homogenizer to obtain a collagen homogenate. Step 3, Preparation of oxidized sodium hyaluronate Sodium hyaluronate solution was subjected to aldehyde reaction with sodium periodate, the reaction was terminated by adding ethylene glycol, and then concentrated by ultrafiltration and lyophilized to obtain oxidized hyaluronic acid. Step 4, Preparation of hydrogel Oxidized hyaluronic acid was dissolved in a buffer solution to obtain an oxidized hyaluronic acid solution. Collagen homogenate was added to the solution to carry out a cross-linking reaction to form a solidified hydrogel. After washing to remove residual unreacted oxidized hyaluronic acid, the initial hydrogel was obtained. The initial hydrogel was then coated with sulfonated chitosan and trehalose to obtain a hydrogel block, which is the collagen hydrogel.
2. The method for preparing a collagen hydrogel crosslinked with oxidized hyaluronic acid according to claim 1, characterized in that, In step one, the collagen is collagen extracted from animal Achilles tendon or animal skin; the concentration of the collagen solution is 1-6 mg / mL; adjusting the pH to the isoelectric point means adjusting the pH to 4.5-6.0; the pH adjuster is one or more of sodium hydroxide, disodium hydrogen phosphate, sodium citrate, and citric acid.
3. The method for preparing a collagen hydrogel crosslinked with oxidized hyaluronic acid according to claim 1, characterized in that, The collagen pretreatment steps include: adjusting the pH of the collagen solution to 4.5-6.0, stirring to precipitate, centrifuging to obtain the precipitate, and repeatedly centrifuging and washing with buffer solution to obtain crude collagen fiber precipitate; resolving the crude collagen fiber precipitate with acetic acid solution, stirring at 3-5℃, adjusting the pH to 2-3, adding pepsin solution, and carrying out a constant temperature reaction; after the reaction is completed, terminating the reaction by adjusting the pH to inactivate pepsin, and purifying by tangential flow ultrafiltration to obtain pretreated collagen; wherein the centrifugation speed is 6000-10000 rpm and the centrifugation time is 15-20 min.
4. The method for preparing a collagen hydrogel crosslinked with oxidized hyaluronic acid according to claim 1, characterized in that, In step two, the high-pressure homogenization is carried out in three stages: the first stage pressure is 4000±100psi; the second stage pressure is 8000±100psi; and the third stage pressure is 12000±100psi. The high-pressure homogenization temperature is controlled at 2-8℃. The concentration of the collagen homogenate is 50-70mg / mL.
5. The method for preparing a collagen hydrogel crosslinked with oxidized hyaluronic acid according to claim 1, characterized in that, In step three, the mass concentration of the sodium hyaluronate solution is 0.5-5%; the mass ratio of sodium hyaluronate to sodium periodate is 1:0.5-1:
2.
6. The method for preparing a collagen hydrogel crosslinked with oxidized hyaluronic acid according to claim 1, characterized in that, In step four, the mass concentration of the oxidized hyaluronic acid solution is 3%; the mass ratio of the collagen homogenate to the oxidized hyaluronic acid solution is 1:1-5:1; the cross-linking reaction temperature is 37℃ and the cross-linking reaction time is 1-3h.
7. The method for preparing a collagen hydrogel crosslinked with oxidized hyaluronic acid according to claim 1, characterized in that, In step four, the cleaning step includes: dividing the solidified hydrogel into portions with a volume of 0.1-1 cm³. 3 The small pieces of gel were soaked in PBS solution and stirred for 2-4 hours. The supernatant was removed by centrifugation, and the washing operation was repeated 3-5 times to obtain the initial hydrogel.
8. The method for preparing a collagen hydrogel crosslinked with oxidized hyaluronic acid according to claim 1, characterized in that, In step four, the sulfonated chitosan composite step includes immersing the initial hydrogel in a sulfonated chitosan solution and obtaining a sulfonated chitosan composite hydrogel through vacuum negative pressure permeation; the trehalose coating step includes placing the sulfonated chitosan composite hydrogel in a trehalose solution and treating it under vacuum negative pressure to obtain a hydrogel block.
9. The method for preparing a collagen hydrogel crosslinked with oxidized hyaluronic acid according to claim 8, characterized in that, The steps for sulfonated chitosan composite hydrogel include: soaking the initial hydrogel block in PBS buffer at 3-5℃, treating it with 0.1% EDTA solution, then adding it to a 30-50 g / L sulfonated chitosan solution, soaking it for 1-3 hours under vacuum of -0.08±0.01 MPa and temperature of 3-5℃, then raising the temperature to 25-27℃ and controlling the pH at 6.0±0.1, and reacting at a constant temperature. After the reaction, rinsing with PBS buffer to remove unbound sulfonated chitosan to obtain sulfonated chitosan composite hydrogel; the steps for trehalose coating include: placing the sulfonated chitosan composite hydrogel in a mixed solution containing 25-35 g / L trehalose, 0.1% hydroxypropyl methylcellulose, and 0.1M PBS, controlling the temperature at 3-5℃, treating it under negative pressure for 2-4 hours, and then allowing it to stand at normal pressure for 1-3 hours to obtain hydrogel block.
10. A hydrogel prepared by the method for preparing a collagen hydrogel crosslinked with oxidized hyaluronic acid according to any one of claims 1-9, characterized in that, The application of the hydrogel in the preparation of long-acting implantable formulations.
Citation Information
Patent Citations
Preparation method and applications of chitosan polypeptide derivative self-cross-linking hydrogel taking oxidized hyaluronic acid as cross-linking agent
CN111019162A
Preparation method of medical grade III-type collagen and III-type collagen
CN115572328A
Long-acting collagen fiber and preparation method thereof
CN116103776A
Wound repair material as well as preparation method and application thereof
CN120305450A
Hyaluronic acid-collagen composite hydrogel for injection and preparation method thereof
CN103333349A